EXPERIMENTAL AND NUMERICAL APPROACH TO FLOW LOSS ESTIMATION IN A HYDRAULIC PIPE SEGMENT - Biluš, Ignacijo; Klasinc, Roman; Predin, Andrej (Journal of Energy Technology, 2024)
Energy demand is expected to rise in the future and, accordingly, new, optimised solutions should be introduced. This paper presents a study made at the Graz University of Technology analysing the flow losses in the hydraulic pipe junction. The basic idea of the research was to implement modern, computer-based simulation to olsandto apply them to the findings of the model tests performed in the laboratory. The goal of present study was to assure the long term cavitation-safe operationofahydraulicpipejunctionwithanozzle. This paper demonstrates the possibilities and difficulties of using computational fluid dynamics (CFD) in the process off low loss coefficient determination. There sultss how that the numerical model with a conventional closure model should be used for the determination of phenomena attheintegral point of view.
Keywords: Numerical modelling; CFD; flow losses; measurements; cavitation